Development of fragility curves for tuned mass damper inerter (TMDI) systems under pulse-like ground motions from the 2024 Noto earthquake (Mw 7.6) - Beerabbi Eshapurada, Madhu; Reddy, K. S. K. Karthik (Frontiers in Built Environment, 2026)
Enhancing seismic resilience in the built environment is essential for safeguarding structures in earthquake-prone regions. Inerter-based vibration control systems represent an important advancement in earthquake engineering, yet their effectiveness under pulse-like, near-fault ground motions has not been thoroughly evaluated. This study investigates the seismic response of building structures equipped with tuned mass damper inerter (TMDI) systems when subjected to intense, pulse-like excitations, with reference to the 2024 Noto earthquake in Japan (Mw 7.6). Through comprehensive simulation of low, medium, and high-rise structural models, spanning fundamental periods of 0.5, 1.0, and 2.0 s, the research assesses TMDI performance across varying mass ratios. Results indicate notable reductions in seismic vulnerability and damage potential, with performance gains validated against HAZUS fragility benchmarks for comparable structures demonstrating up to 145% improvement in median PGA for slight damage and 167% for moderate damage states. The findings underscore the potential of TMDIs as scalable, innovative vibration control solutions, contributing to safer and more sustainable built environments in near-fault seismic regions worldwide.